Penegakan Hukum Administrasi Terhadap Pegawai Lapas Yang Terlibat Penyebaran Narkotika Di Dalam Lapas Kelas II A Ambon - Sattu, Mayakarin Fiadolla; Salmon, Hendrik; Tita, Heillen Martha Yosephine (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
The aim of this research is to analyze and find out about the classification of abuse of authority by Correctional Institution officers who distribute narcotics and to find out disciplinary sanctions for Correctional Institution officers who distribute narcotics according to Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. The research method used is the normative legal type. Based on the results obtained (1) The classification of abuse of authority carried out by correctional institution officers regarding the distribution of narcotics that occurs in prisons, in essence, is that a prison officer has an obligation that he must carry out in prison. (2) Disciplinary sanctions for Correctional Institution officers who distribute narcotics according to Government Regulation Number 94 of 2021 concerning Civil Servant discipline are in the form of lighter disciplinary and administrative sanctions compared to Government Regulation Number 53 of 2010, namely Respectful Dismissal Not at Your Own Request. Where there is still a gap in Government Regulation Number 94 of 2021 concerning Civil Servant discipline for abusers who have civil servant status to receive pension benefits if they meet the criteria.